If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(1 + 7n) = -19 + -1n (1 * 3 + 7n * 3) = -19 + -1n (3 + 21n) = -19 + -1n Solving 3 + 21n = -19 + -1n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add 'n' to each side of the equation. 3 + 21n + n = -19 + -1n + n Combine like terms: 21n + n = 22n 3 + 22n = -19 + -1n + n Combine like terms: -1n + n = 0 3 + 22n = -19 + 0 3 + 22n = -19 Add '-3' to each side of the equation. 3 + -3 + 22n = -19 + -3 Combine like terms: 3 + -3 = 0 0 + 22n = -19 + -3 22n = -19 + -3 Combine like terms: -19 + -3 = -22 22n = -22 Divide each side by '22'. n = -1 Simplifying n = -1
| 1.4a-12.4=5.6 | | 70-2x=34+18 | | 5c+13=73 | | 12b+14=7b-29 | | 7(2+3x)=203 | | 11470=1998+74h+54h | | 3y-18+4=-14 | | y=2(2x+1) | | 2x^2+(k+8)x+(k+24)=0 | | 12y=19 | | T=0.15x+35 | | 2x^2+8x=5x+35 | | 2y+8=2x | | 5(6x+10)=3350 | | 8-(x+5)=31 | | 3x-9=8x+4 | | 4(3x+1)=88 | | 4y+8=22 | | 6(4+x)=24 | | 1803516=a-483948 | | 2-3u=14 | | 8(m-1)+6=-40+6m | | 2.2+0.3x=0.1 | | 8+2(x-4)=12 | | -z+7=0 | | ln(x)+ln(x-6)=5 | | 6(8+3x)=210 | | 7(3x+6)=126 | | y+4x+6=0 | | -5+25x-40x+-10=-12x | | 3(2a-4)=8a-15 | | 2x-50=-10x+10 |